Immunization with 60kD Ro peptide produces different stages of preclinical autoimmunity in a Sjögren's syndrome model among multiple strains of inbred mice - Kurien, B T; Dsouza, A; Igoe, A; Lee, Y J; Maier-Moore, J S; Gordon, T; Jackson, M; Scofield, R H (Clinical and experimental immunology, 2013)
Summary Sjögren's syndrome is a chronic illness manifested characteristically by immune injury to the salivary and lacrimal glands, resulting in dry mouth/eyes. Anti-Ro [Sjögren's syndrome antigen A (SSA)] and anti-La [Sjögren's syndrome antigen B (SSB)] autoantibodies are found frequently in Sjögren's subjects as well as in individuals who will go on to develop the disease. Immunization of BALB/c mice with Ro60 peptides results in epitope spreading with anti-Ro and anti-La along with lymphocyte infiltration of salivary glands similar to human Sjögren's. In addition, these animals have poor salivary function/low saliva volume. In this study, we examined whether Ro-peptide immunization produces a Sjögren's-like illness in other strains of mice. BALB/c, DBA-2, PL/J, SJL/J and C57BL/6 mice were immunized with Ro60 peptide-274. Sera from these mice were studied by immunoblot and enzyme-linked immunosorbent assay for autoantibodies. Timed salivary flow was determined after pharmacological stimulation, and salivary glands were examined pathologically. We found that SJL/J mice had no immune response to the peptide from Ro60, while C57BL/6 mice produced antibodies that bound the peptide but had no epitope spreading. PL/J mice had epitope spreading to other structures of Ro60 as well as to La, but like C57BL/6 and SJL/J had no salivary gland lymphocytic infiltration and no decrement of salivary function. DBA-2 and BALB/c mice had infiltration but only BALB/c had decreased salivary function. The immunological processes leading to a Sjögren's-like illness after Ro-peptide immunization were interrupted in a stepwise fashion in these differing mice strains. These data suggest that this is a model of preclinical disease with genetic control for epitope spreading, lymphocytic infiltration and glandular dysfunction. [PUBLICATION ABSTRACT]